PERSEPSI AUDITOR BPK RI DAN PENGGUNA LAPORAN KEUANGAN MENGENAI TANGGUNGJAWAB AUDITOR, KEANDALAN AUDIT DAN KEGUNAAN LAPORAN KEUANGAN AUDITAN - Angga Anugrawan; Paulus Th Basuki Hadiprajitno (Diponegoro Journal of Accounting, 2016)
This study aims to identify the factors that are causing perception between auditors and users of financial statements, and empirically examine the factors that is responsible auditor, audit reliability and usefulness of audited financial statements.This research was conducted by questionnaire to auditors and users of financial statements using a Likert scale in government agencies Semarang and analyzed with different test t independent tests are aimed at determining whether two samples of unrelated had an average of different and compare the average two groups that do not relate to each other. Are these two groups have an average value that is equal or not significantly.The results showed that of the three factors that is the responsibility of the auditor, the audit reliability and usefulness of the audited financial statements there were no differences of perception significantly after hypothesis test using different test independent t tests, but after a thorough test by testing hypotheses pernyataan- statements that represent each of these factors there is a difference in one statement of responsibility factor auditor to express an auditor does not have the responsibility to prepare financial statements auditee.